Improvement Strategies, Cost Effective Production, and Potential Applications of Fungal Glucose Oxidase (GOD): Current Updates - Dubey, Manish K.; Zehra, Andleeb; Aamir, Mohd; Meena, Mukesh; Ahirwal, Laxmi; Singh, Siddhartha; Shukla, Shruti; Upadhyay, Ram S.; Bueno-Mari, Ruben; Bajpai, Vivek K. (Frontiers in Microbiology, 2017)
Fungal glucose oxidase (GOD) is widely employed in the different sectors of food industries for use in baking products, dry egg powder, beverages, and gluconic acid production. GOD also has several other novel applications in chemical, pharmaceutical, textile and other biotechnological industries. The electrochemical suitability of GOD catalyzed reactions has enabled its successful use in bioelectronic devices, particularly biofuel cells, and biosensors. Other crucial aspects of GOD such as improved feeding efficiency in response to GOD supplemental diet, roles in antimicrobial activities and enhancing pathogen defense response, thereby providing induced resistance in plants have also been reported. Moreover, the medical science, another emerging branch where GOD was recently reported to induce several apoptosis characteristics as well as cellular senescence by downregulating Klotho gene expression. These widespread applications of GOD have led to increased demand for more extensive research to improve its production, characterization, and enhanced stability to enable long term usages. Currently, GOD is mainly produced and purified from Aspergillus niger and Penicillium species, but the yield is relatively low and the purification process is troublesome. It is practical to build an excellent GOD-producing strain. Therefore, the present review describes innovative methods of enhancing fungal GOD production by using genetic and non-genetic approaches in-depth along with purification techniques. The review also highlights current research progress in the cost effective production of GOD, including key advances, potential applications and limitations. Therefore, there is an extensive need to commercialize these processes by developing and optimizing novel strategies for cost effective GOD production.